PERANAN GURU PENDAMPING KHUSUS DALAM MEMFASILITASI PEMBELAJARAN INKLUSI DI SEKOLAH INKLUSI - Mahya, Yogi Muthohir Zuhad; Rabbani, Khafidh Fardan; Saputra, Dwi; Minsih, Minsih (JPI (Jurnal Pendidikan Inklusi), 2022)
Abstract In inclusive education programs, special assistant teachers are one element that has a very important role. This research aims to: 1) Describe the role of special assistant teachers at MIM PK Kartasura and 2) How to facilitate learning for children with special needs at MIM PK Kartasura. The research method used is descriptive qualitative research, using interview, observation and documentation data collection techniques. The validity used to test the validity of the data is triangulation. Data analysis uses power triangulation. The subjects of this research include the school principal, four special assistant teachers, and two children with special needs, while the object of the research is the role of special assistant teachers in facilitating inclusive learning in schools. The results of the research show that: 1) The role of special assistant teachers is: carrying out the initial identification process, conducting assessments, reviewing evaluations, creating individual learning programs, providing learning assistance to children with special needs, assessing the learning of children with special needs, needs and intensive special assistance. 2) Special accompanying teachers in facilitating inclusive learning for students with special needs are carried out by adapting to the students' conditions. In facilitating students with special needs special accompanying teachers collaborate with class teachers. Forms of collaboration include: providing suggestions for effective learning strategies, providing training to support students, helping design Individual Learning Plans (RPI).